Maritime Supply Chain Optimisation: A Case Study of Blockchain Integration in Port Logistics Management - Karjono, Karjono; Kusumawati, Evyana Diah; Pambudi, M. Aji Luhur; Karmanis, Karmanis (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2024)
This research examines the potential for maritime supply chain optimisation through the integration of blockchain technology in port logistics management. In the era of global digitalisation, the maritime sector faces challenges to improve operational efficiency and transparency. This study uses a case study approach to evaluate the implementation of blockchain in one of Indonesia's major ports. The research methodology involved qualitative and quantitative analyses, including interviews with key stakeholders, direct observation of logistics processes, and analysis of historical port operational data. The blockchain system was implemented over a six-month period, and its performance was compared with conventional logistics management systems. Key challenges identified include the need for a large initial investment, resistance to change from some stakeholders, and the need for industry-wide standardisation of blockchain protocols. This research demonstrates the great potential of blockchain technology in optimising maritime supply chains. Recommendations for further implementation and future research are discussed, with an emphasis on the importance of industry collaboration and regulatory support to accelerate the adoption of this technology in the maritime sector.